2019
DOI: 10.1111/liv.14092
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between coronary artery disease and cardiovascular events early after liver transplantation

Abstract: Background & Aims: Cardiovascular complications are major contributors to mortality at liver transplantation (LT). However, the impact of coronary artery disease (CAD) on these complications is not well-understood as the literature is limited by non-invasive assessment of CAD, which is suboptimal in patients with cirrhosis. Thus, the current study evaluated cardiovascular events at LT stratified according to the presence and severity of CAD quantified on coronary angiography. ated (N = 348), but analysis was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…This could be partly related to the fact that these patients were already being managed for CAD prior to LT and may have received more intensive monitoring after LT. The same group showed that diabetes was associated with an increased risk of having a cardiovascular event, and statin use demonstrated a survival benefit in patients who have undergone LT. 90,91 This supports earlier studies demonstrating the association of MetS with CV complications, thus necessitating early identification and aggressive modification of MetS to improve outcomes.…”
Section: Cardiovascular Disease/perioperative Risksupporting
confidence: 82%
See 1 more Smart Citation
“…This could be partly related to the fact that these patients were already being managed for CAD prior to LT and may have received more intensive monitoring after LT. The same group showed that diabetes was associated with an increased risk of having a cardiovascular event, and statin use demonstrated a survival benefit in patients who have undergone LT. 90,91 This supports earlier studies demonstrating the association of MetS with CV complications, thus necessitating early identification and aggressive modification of MetS to improve outcomes.…”
Section: Cardiovascular Disease/perioperative Risksupporting
confidence: 82%
“…89 Interestingly, coronary artery disease (CAD) does not seem to confer an increased risk of CVD mortality in transplant patients. 90 Patel et al recently reported that pre-LT CAD presence and severity did not impact survival after LT. This could be partly related to the fact that these patients were already being managed for CAD prior to LT and may have received more intensive monitoring after LT.…”
Section: Cardiovascular Disease/perioperative Riskmentioning
confidence: 97%
“…Cirrhotic cardiomyopathy is a common consequence of cirrhosis, affecting about one third of patients [65]. Coronary artery diseases are also frequent comorbidities as cardiovascular risk factors are more prevalent in this population, especially diabetes [66,67].…”
Section: Is Cardio-respiratory Sarcopenia Frequent In Patients With Cmentioning
confidence: 99%
“…Although studies have demonstrated that the degree of coronary disease on catheterization at the time of transplant does not predict survival, it is notable that all included patients found to have obstructive disease had revascularization performed prior to transplant, thereby altering the natural course of the disease 17,18 . We now have a decade of data demonstrating the 1‐year survival impact of catheterization and associated coronary intervention, underscoring its importance in the risk stratification process 19,20 .…”
Section: Catheterization Is Safe and Intervening Makes A Differencementioning
confidence: 99%
“…15,16 Although studies have demonstrated that the degree of coronary disease on catheterization at the time of transplant does not predict survival, it is notable that all included patients found to have obstructive disease had revascularization performed prior to transplant, thereby altering the natural course of the disease. 17,18 We now have a decade of data demonstrating the 1-year survival impact of catheterization and associated coronary intervention, underscoring its importance in the risk stratification process. 19,20 Beyond percutaneous coronary intervention (PCI), catheterization also allows the identification of more subtle evidence of coronary artery disease (CAD), potentially giving more evidence to modify the patient's risk with statin therapy, an intervention that is significantly underused in this population.…”
Section: Catheterization Is Safe and Intervening Makes A Differencementioning
confidence: 99%